Symphony of secrets eaudiobook - Slocumb, Brendan (Books on Tape, 2023)
A gripping page-turner from the celebrated author of book club favorite The Violin Conspiracy : Music professor Bern Hendricks discovers a shocking secret about the most famous American composer of all time—his music may have been stolen from a Black Jazz Age prodigy named Josephine Reed. Determined to uncover the truth that a powerful organization wants to keep hidden, Bern will stop at nothing to right history's wrongs and give Josephine the recognition she deserves. “A maestro of musical mystery...Slocumb’s writing is invigorating, and the detail in his character work makes the main characters in both time periods easy to root for.... Thrilling.” — The New York Times "At once a celebration of music and also a cautionary tale about legacy, privilege, and creative genius." —Nita Prose, #1 New York Times bestselling author of The Maid Bern Hendricks has just received the call of a lifetime. As one of the world’s preeminent experts on the famed twentieth-century composer Frederick Delaney, Bern knows everything there is to know about the man behind the music. When Mallory Roberts, a board member of the distinguished Delaney Foundation and direct descendant of the man himself, asks for Bern’s help authenticating a newly discovered piece, which may be his famous lost opera, RED , he jumps at the chance. With the help of his tech-savvy acquaintance Eboni, Bern soon discovers that the truth is far more complicated than history would have them believe. In 1920s Manhattan, Josephine Reed is living on the streets and frequenting jazz clubs when she meets the struggling musician Fred Delaney. But where young Delaney struggles, Josephine soars. She’s a natural prodigy who hears beautiful music in the sounds of the world around her. With Josephine as his silent partner, Delaney’s career takes off—but who is the real genius here? In the present day, Bern and Eboni begin to uncover more clues that indicate Delaney may have had help in composing his most successful work. Armed with more questions than answers and caught in the crosshairs of a powerful organization who will stop at nothing to keep their secret hidden, Bern and Eboni will move heaven and earth in their dogged quest to right history’s wrongs.